Indium Bromide-catalyzed Unprecedented Hydrogenolysis: A Novel One-Pot Synthesis of Per-O-Acetylated β-carboxymethyl O and S-glycosides - Yadav, Ram N.; Singh, Amrendra K; Banik, Bimal (Current Organic Chemistry, 2020)
Numerous O (oxa)- and S (thia)-glycosyl esters and their analogous glycosyl acids have been accomplished through stereoselective glycosylation of various peracetylated bromo sugar with benzyl glycolate using InBr3 as a glycosyl promotor followed by in situ hydrogenolysis of resulting glycosyl ester. A tandem glycosylating and hydrogenolytic activity of InBr3 has been successfully investigated in a one-pot procedure. The resulting synthetically valuable and virtually unexplored class of β-CMGL (glycosyl acids) could serve as an excellent potential chiral auxiliary in the asymmetric synthesis of a wide range of enantiomerically pure medicinally prevalent β-lactams and other bioactive molecules of diverse medicinal interest.
Keywords: glycosylation